Stock Broker Summary History Analisys Volume Value Frequency And Price Accumulation - Evan Zovinul; Rahila Rahila; Nizwan Zukhri ; Darus Altin (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This writing aims to find out how much accumulation and the value of the average fair price of shares carried out by Securities Companies in their stock summary history. This research will be one of the basic alternatives in determining investment actions. Shares are a type of high-risk investment (Arora, S., & Marwaha, K. 2014), an analytical decision in buying or selling shares is not an easy thing, there are many factors that influence the increase or decrease in share prices, in this research the author took secondary data from the Internet, namely; Securities Company/Company Code, history/historical data, Technical Indicators, Share Volume, Rupiah Value/Share Value and Share Price. Answering the research gap, the author analyzed the data above by observing the average value in a certain time interval 1 January 2022 - 31 December 2022, which in the process of writing this secondary data was processed using the SPSS application. The aim is to obtain a reasonable average share price at maximum capitalization by the securities company. Furthermore, to be able to carry out further research to reveal the fair average share price, you can analyze various share categorizations (BlueChip, SecondLiner, Cyclical Industry, Financial Industry, etc.)